QIYAS SEBAGAI SUMBER HUKUM ISLAM - Maimun Abdurrahman Amin (SYARIAH: Journal of Islamic Law, 2022)
In Islamic law, qiyas is a solution offered for various legal cases that are not explicitly stated in the proposition in the sources of Islamic law. It is known that Imam Shafi'i was the originator of the concept of qiyas. In his view, various legal cases in Muslim societies that are not clearly regulated in the Qur'an or Sunnah can be resolved through qiyas, either in the form of qiyas jaly or qiyas khafi. Everyone knows that Islamic law is contained in the Koran, the prophetic traditions, the opinions of the early generations of scholars, the consensus and controversies among them, has a high intellectual capacity and sharp analysis whereby he can identify obscure facts, and can become al-Qais. The concept of qiyas consists of four elements of al-ashl, namely the original law derived from the text, al-far, or from an al-'illah. A qiyas may not go beyond the text of the main sources of Islamic law, because it is taken from existing texts.